2019
DOI: 10.1177/0141778919850003
|View full text |Cite
|
Sign up to set email alerts
|

Abortion and Reproduction in Ireland: Shame, Nation-building and the Affective Politics of Place

Abstract: In 2018, Irish citizens voted overwhelmingly to repeal the Eighth Amendment to the Constitution to allow for the introduction of a more liberal abortion law. In this article, I develop a retrospective reading of the stubborn persistence of the denial of reproductive rights to women in Ireland over the decades. I argue that the ban’s severity and longevity is rooted in deep-seated, affective attachments that formed part of processes of postcolonial nation-building and relied on shame and the construction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Her interpretation that the public were encouraged to vote ‘Yes’ as an act of ‘charity’ warrants specific analysis. The tendency to base policy on charity rather than on the principles of social justice is, according to Fischer (2020), a quintessentially Irish facticity, imbricated in Ireland's postcolonial identity, which is contingent on the notion of Irish people as inherently ‘morally superior’ to their colonialist, British counterparts (Fischer, 2019). In the early years of independence, this moral superiority was secured through the regulation of female sexual behaviour – the moral purity of the nation bound up in the sexual chastity of Irish women (Fischer, 2019).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Her interpretation that the public were encouraged to vote ‘Yes’ as an act of ‘charity’ warrants specific analysis. The tendency to base policy on charity rather than on the principles of social justice is, according to Fischer (2020), a quintessentially Irish facticity, imbricated in Ireland's postcolonial identity, which is contingent on the notion of Irish people as inherently ‘morally superior’ to their colonialist, British counterparts (Fischer, 2019). In the early years of independence, this moral superiority was secured through the regulation of female sexual behaviour – the moral purity of the nation bound up in the sexual chastity of Irish women (Fischer, 2019).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In the early years of independence, this moral superiority was secured through the regulation of female sexual behaviourthe moral purity of the nation bound up in the sexual chastity of Irish women (Fischer, 2019). In this vein, the criminalisation of abortion and the Irish respect for 'unborn life' became symptomatic of the country's (Catholic) virtuousness, in opposition to (Protestant) England where abortion was available (Fischer, 2019). Hogan (2019) explains how the religious orders which ran 'Mother and Baby Homes' workhouses for 'unmarried mothers'also constructed themselves as acting out of benevolence for 'fallen' women who would otherwise be scorned by society for their 'transgressions'.…”
Section: Shame Postcoloniality and Reconstituting Irishnessmentioning
confidence: 99%
“…Symphysiotomy was rarely practised in the rest of Europe after the 1950s, but an estimated 1,500 Irish women experienced this procedure between 1940 and 1990 (Khaleeli, 2014). The practice continued for a variety of reasons: a Catholic aversion to Caesarean sections (which, it was believed, could limit the number of children that a woman can bear), the need to train medical students in procedures that could be carried out without electricity in rural parts of the world where they would later practise, including nations in Africa, and a general disregard for women's autonomy and well-being for the sake of the cause of continued reproduction (Fischer, 2019;Khaleeli, 2014).…”
Section: Obstetric Violencementioning
confidence: 99%
“…The diluted TFY message seemed contrary to the inclusivity of caring-with as developed within our community of activists. It also felt like a concession to the Catholic Church's denigration of women's bodily autonomy (Fischer, 2019). One study of debates on the message boards of Irish national newspapers showed that some Catholics can reconcile a right to abortion with their personal faith (Sambaraju et al, 2018).…”
Section: Power-to: Feminist Agency and Participatory Democracymentioning
confidence: 99%